The Contribution of Social and Environmental Factors to Race Differences in Dental Services Use - Eisen, Colby H. (J Urban Health, 2015)
Dental services use is a public health issue that varies by race. African Americans are less likely than whites to make use of these services. While several explanations exist, little is known about the role of segregation in understanding this race difference. Most research does not account for the confounding of race, socioeconomic status, and segregation. Using cross-sectional data from the Exploring Health Disparities in Integrated Communities Study, we examined the relationship between race and dental services use. Our primary outcome of interest was dental services use within 2 years. Our main independent variable was self-identified race. Of the 1408 study participants, 59.3 % were African American. More African Americans used dental services within 2 years than whites. After adjusting for age, gender, marital status, income, education, insurance, self-rated health, and number of comorbidities, African Americans had greater odds of having used services (odds ratio = 1.48, 95 % confidence interval 1.16, 1.89) within 2 years. Within this low-income racially integrated sample, African Americans participated in dental services more than whites. Place of living is an important factor to consider when seeking to understand race differences in dental service use.